2010
DOI: 10.1002/nur.20392
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vascular leg disorders on physical activity in methadone‐maintained adults

Abstract: Chronic venous disorders (CVD) and peripheral arterial disease (PAD) may affect diverse physical activity domains. How CVD and PAD and other relevant variables affect physical activity was examined in 569 opioid-addicted adults. Both CVD and PAD were significantly inversely related to daily walking, sports, and active living. Effects remained significant in the latent variable regression after controlling covariates. Overall activity was very low; most participants walked less than a half mile daily and rarely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…While studies have been conducted that include OUD patients, most studies in our review were conducted with subjects recovering from various SUDs. Only 2 studies 18,24 solely examined the role of exercise in an OUD recovery group. Cocaine was the most common substance included in the studies, identified in 13 of 18 articles, with alcohol use next most common, identified in 9 of 18 articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies have been conducted that include OUD patients, most studies in our review were conducted with subjects recovering from various SUDs. Only 2 studies 18,24 solely examined the role of exercise in an OUD recovery group. Cocaine was the most common substance included in the studies, identified in 13 of 18 articles, with alcohol use next most common, identified in 9 of 18 articles.…”
Section: Discussionmentioning
confidence: 99%
“…Two other additional articles were excluded due to discrepancies within the study designs, leaving 18 articles (Figure 1) for full review. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] exercise and strength exercise. Nine of the studies were retrospective in nature.…”
Section: Methodsmentioning
confidence: 99%
“… 24 IDU also has implications for mobility and balance; overall physical activity among PWID is low, and in a stuporous drug state, PWID may have inactive lower extremity muscles with resultant diminished venous return. 27 Injecting into the lower extremities may additionally cause nerve and muscle damage, with resultant impaired calf muscle and ankle joint function; compromised walking mobility has been found to have a direct relationship with severity of CVD in this population. 25 Mobility deficits, such as difficulty walking, climbing stairs, and working, are thus a largely underrecognized consequence of IDU.…”
Section: Overviewmentioning
confidence: 93%
“…Relative to the general population, PWID have an increased prevalence of DVT, which increases the risk of CVD by 25-fold [24]. IDU also has implications for mobility and balance; overall physical activity among PWID is low, and in a stuporous drug state, PWID may have inactive lower extremity muscles with resultant diminished venous return [27].…”
Section: Idu: Infections Wounds and Other Implicationsmentioning
confidence: 99%
“…Recent pilot studies have assessed the efficacy of exercise, a structured and planned form of physical activity, interventions in addressing drug (Brown, et al, 2010), marijuana (Buchowski, et al, 2011), and alcohol (Brown, et al, 2009) misuse, with positive results (Weinstock, Barry, & Petry, 2008). However, to our knowledge only one study has assessed activity level and motivation to exercise in MMT patients; they found low levels of physical activity in MMT participants, but encouragingly, motivation to exercise was the best predictor of physical activity (Pieper, Templin, Kirsner, & Birk, 2010). Understanding benefits and barriers to exercise as well as level of physical activity in a MMT population may be important to motivate this group to increase physical activity.…”
Section: 0 Introductionmentioning
confidence: 99%